Penerapan Teknologi Pendidikan: Menghadapi Kendala, Menciptakan Solusi - Milla, Daindo; Zulkipli, Zulkipli; Sahar, Adnan; Reliubun, Abdurrahman Shaleh; Amri, Haerul (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to identify obstacles and solutions in the application of educational technology through literature review. Technology has great potential in improving the quality of learning, but its application in the field still faces various obstacles. This research uses a qualitative approach with a literature review method. The sources used include academic journals, scientific articles, government reports, and publications from relevant national and international educational institutions. The data obtained is analyzed thematically by identifying the main categories that emerge from the literature. This literature review reveals four main obstacles in the application of educational technology, namely the lack of adequate infrastructure, limited technological competence among educators, resistance to change, and lack of policy support from the government and educational institutions. To overcome these obstacles, several solutions are recommended, including increasing equitable access to technology infrastructure, providing sustainable technology training for educators, implementing an adaptive approach in the technology integration process, and strengthening policies that support technology adoption in education